La rappresentazione del corpo delle donne. Strumenti, teorie e pratiche di sorveglianza - Lucia Miodini (Storia delle Donne)
The essay traces a wide critical survey, rich in analytical insights, of the history of the representation of the female body as a field of investigation, from the early nineteenth century to the beginning of the twentieth century. Paradigmatic cases of the social marginalization of women are presented: the discursive formation of physiognomy; the medical thought of the nineteenth century; the link between female sexuality and deviance of criminal anthropology. The study of medical sources and public opinion, from a gender perspective, transdisciplinary, focuses on current ideas about women’s nature; value prescriptions and normative prejudices. In this historical path, medical, psychiatric and judicial photography plays an essential role as a tool for control, measurement and cataloging. The study addresses the construction of a gender imaginary through the analysis of photographic atlas made in the second half of the nineteenth century, which encode and systematize the fear of the female sexuated body. The history of the critical debate on criminal anthropology and the historiography on photography in the nineteenth and early twentieth centuries in Italy serves to understand the persistence of gender imagery in contemporary; and to understand the survival of normative stereotypes, of extreme significance in the current political scene.